Promoting Social Communication in a Child With Specific Language Impairment. (August 2016) - O'Handley, Roderick D.; Radley, Keith C.; Lum, John D. K.
Social difficulties represent a major area of concern in children with specific language impairment (SLI). Social skills interventions targeting communication or language skills of children with SLI have been generally ineffective. The current study tested the efficacy of a social skills intervention consisting of multiple behavioral interventions to increase nonverbal, verbal, and turn-taking conversation skills of an 8-year-old male with SLI. Using a multiple baseline across skills design, data were collected in a university clinic setting. Visual analysis indicated that when training for a target skill was introduced, percentage of skill steps successfully demonstrated increased. In addition, pre- and postintervention standardized rating scales completed by parents and teachers indicated improvements in pragmatic skill use in nontraining environments. Results and implications are described in terms of utilization of interventions for pragmatic skills of children with SLI.